2017
DOI: 10.17582/journal.aavs/2017/5.11.449.455
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mint Leaves with or without Enzyme Supplementation on Blood Biochemistry, Carcass Characteristics and Sensory Attributes of Broiler Chicken

Abstract: | A study was conducted to evaluate the effect of dietary supplementation of Mint leaves (Mentha piperita) with or without enzyme treatment on blood chemistry, carcass characteristics and sensory attributes of broiler chicken production. 225 day old commercial broiler chicks reared together until 7 days of age. On 8th day, the chicks were individually weighed, distributed randomly into 5 treatment groups of 3 replicates with 15 chicks each for a period of 42 days of age. Birds in the control group (T1) were fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
2
7
2
Order By: Relevance
“…The variables that show statistical differences tend to decrease, since they are the groups that received the infusion. This differs from that mentioned by Khursheed et al (2017), who did not find significant statistical differences in data obtained from the commercial broiler chicken channel in an experiment where fresh mint leaves were administere with and without enzymatic supplementation to evaluate blood biochemistry, carcass characteristics and sensory attributes. It also differs from that reported by Ameri et al (2016), regarding to the characteristics of the carcass.…”
Section: Live Weightcontrasting
confidence: 99%
See 1 more Smart Citation
“…The variables that show statistical differences tend to decrease, since they are the groups that received the infusion. This differs from that mentioned by Khursheed et al (2017), who did not find significant statistical differences in data obtained from the commercial broiler chicken channel in an experiment where fresh mint leaves were administere with and without enzymatic supplementation to evaluate blood biochemistry, carcass characteristics and sensory attributes. It also differs from that reported by Ameri et al (2016), regarding to the characteristics of the carcass.…”
Section: Live Weightcontrasting
confidence: 99%
“…The juiciness ( Figure 3) shows arithmetical differences in all treatments being pleasant for the majority of respondents, but statistically, T3, T4 and T5 differ from the control. These results differ from those reported by Khursheed et al (2017), who used a panel of experts, not find significant statistical differences from sensory analysis of meat. Meat colour was not evaluate.…”
Section: Organoleptic Characteristicscontrasting
confidence: 99%
“…The results shown in Table 3 are in accord with that of Khursheed et al (2017), who found that the carcass characteristics of birds fed on mint leaves and super doses of phytase enzyme supplement. There was nonsignificant difference in the yield characteristics of gizzard, heart, shank, head and liver weights among different treatment groups and the control group.…”
Section: Gastrointestinal Tractsupporting
confidence: 87%
“…Meanwhile, the chicken supplemented with 1% Spearmint had higher significantly TAC compared with the control group and the other treated groups. Khursheed et al (2017) mentioned that a variety of essential oil compounds, such as menthone, menthol and geraniol have been shown to suppress the hepatic 3hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase activity. In the present study, the no significant effect on serum cholesterol level may be related to relatively low doses of mint which might have implicated in the failure of mint to reduce plasma cholesterol levels Aghazadeh et al, (2011) reported that total cholesterol concentrations were significantly reduced by Mint extract treatments compared to the control group at 21 and 42 d of age.…”
Section: Discussionmentioning
confidence: 99%
“…The method of Koracevic et al, (2001) was used to determine the total antioxidant capacity (TAC) and the Superoxide dismutase (SOD) was determined by the method of Beauchamp and Fridovich, (1971).…”
Section: Antioxidant Statusmentioning
confidence: 99%